IPGRI Annual Report 1998 - International Plant Genetic Resources Institute (International Plant Genetic Resources Institute, 1999)
This report highlights the immediate impact of IPGRI's work by looking at a significant achievement in each of the strategic areas that the Institute pursues. Short introductions to each section illustrate the breadth of IPGRI's research work and the geographical dispersion of its area of operation. The report also contains information for the year 1998 on financial status, Board of Trustees and management team.